The Use of Problem Based Learning With Youtube Media to Improve Listening and Motivation of Junior High School Students - Syakilah Al Mutawakkil Arifin; Khoirul Anwar; Candra Hadi Asmara (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study investigates the use of Problem-Based Learning (PBL) with YouTube media to enhance listening skills and motivation among junior high school students. Conducted at SMP Negeri 3 Gresik, the research employs a mixed-methods approach, combining quantitative and qualitative data. The pre-experimental design assessed students' listening skills before and after a four-week intervention, while questionnaires captured their motivation levels. The findings reveal a significant improvement in students' listening comprehension, as evidenced by an increase in mean test scores from 48.00 in the pre-test to 79.33 in the post-test, with a p-value of 0.000 indicating statistical significance. Additionally, motivation levels improved, with students expressing heightened engagement and interest in the learning process. The integration of authentic and dynamic YouTube content within the PBL framework fostered a more interactive and engaging learning environment, addressing common challenges such as limited motivation and anxiety. The study concludes that the combination of PBL and YouTube media is an effective instructional strategy for enhancing listening skills and motivation in English as a Foreign Language (EFL) contexts. It offers practical insights for educators seeking innovative approaches to language instruction and underscores the importance of integrating technology into active learning methodologies.